Urgensi Pengaturan Hukum Carbon Trading Dalam Kerangka Hukum Lingkungan Indonesia - Edy Lisdiyono; Muhamad Helmi Md Said (PMIH Untag Semarang, 2025)
Climate change is one of the greatest challenges facing humanity in the 21st century. As a country with the third largest tropical forest in the world and a significant carbon emitter, Indonesia plays a strategic role in global greenhouse gas emission reduction efforts. Carbon trading has emerged as an innovative market instrument to promote efficient emission reductions. However, the legal regulation of carbon trading in Indonesia is still partial and lacks a comprehensive legal framework. This paper examines the urgency of establishing integrated carbon trading legal regulation within Indonesia's environmental law framework, analyzes existing regulations, identifies legal vacuums (rechtvacuum), and formulates policy recommendations. The research method used is normative juridical with statutory, conceptual, and comparative approaches. The results show that Indonesia needs a specific law on carbon trading that comprehensively regulates cap-and-trade mechanisms, voluntary carbon markets, registry systems, and dispute resolution mechanisms. Strong regulation will provide legal certainty for investors, encourage green investment, and accelerate Indonesia's transition to a low-carbon economy.